Marketing Mix in Local Market Dynamics: Examining the Impact on Consumer Purchase Decisions at Sinar Bahagia in East Lombok - Rahmatullah, Arwin Yafi; Ramdani, Rizal (Lentera Ilmu Nusantara, 2025)
The development of the business world in the digital era requires companies to implement effective marketing strategies to attract and retain customer loyalty. The marketing mix, which consists of product, price, promotion, and place, is an important strategy for companies in increasing competitiveness. This study aims to analyze the influence of product, price, promotion, and location on the purchasing decisions of Sinar Bahagia consumers. The type of research used is quantitative research. The sample size in this study is 60. The sampling technique used in this study is purposive sampling. The data analysis used is multiple linear regression analysis. The testing tool used is SPSS 25. The results of the study indicate that all components of the marketing mix, including product, price, promotion, and location, have a positive and significant effect on purchasing decisions. The results of this study are expected to provide empirical evidence regarding the dimensions of the marketing mix and serve as a reference for retail businesses in formulating marketing strategies.